A rapid-acting hemostatic hydrogel and its preparation method and application

By preparing a fast-acting hemostatic hydrogel that is cross-linked with microgel and polylysine, the problem of difficulty in controlling massive bleeding in emergency situations was solved, achieving rapid hemostasis and wound healing.

CN120324667BActive Publication Date: 2026-03-20GUANGDONG YUNZHAO MEDICAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510440149.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-09
Publication Date
2026-03-20
Estimated Expiration
2045-04-09

AI Technical Summary

Technical Problem

Existing wound dressings are insufficient to effectively control massive bleeding and promote wound healing in emergency situations, especially deep wounds and complex, irregular wounds caused by small-caliber firearms.

Method used

A fast-acting hemostatic hydrogel, formed by cross-linking microgels with polylysine, is prepared by ultraviolet light cross-linking and Schiff base reaction. It is combined with oxymethacrylic acid, hyaluronic acid, and waterborne polyurethane to form a porous structure for rapid hemostasis.

Benefits of technology

It achieves rapid hemostasis, with hemostasis time of 37 seconds for the liver and within 2 minutes for the abdominal aorta, and a burst pressure of 194.52 mmHg. It also has good tissue adhesion and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120324667B_ABST
    Figure CN120324667B_ABST
Patent Text Reader

Abstract

The application discloses a quick-acting hemostatic hydrogel, which comprises microgels and polylysine, and the mass ratio of the microgels to the polylysine is 1:2 to 2:1, and the microgels comprise oxidized methyl methacrylic hyaluronic acid and aqueous polyurethane. The application further discloses a preparation method of the quick-acting hemostatic hydrogel, and a use for hemostasis or preparation of a hemostatic product. The quick-acting hemostatic hydrogel of the application has viscosity and strength, has the performance of quick blood coagulation and hemostasis, and is beneficial to quick hemostasis of different wounds.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of biomedical materials, and particularly relates to a novel rapid hemostatic hydrogel as well as a preparation method and application thereof. BACKGROUND

[0002] The scientific field of hemostasis and wound repair is facing severe challenges, among which deep wounds caused by small-caliber firearms and complex, irregular and difficult-to-regularly-compress wounds caused by explosive devices in battlefield or emergency situations have become the focus problem that trauma treatment centers urgently need to solve. Uncontrolled bleeding after trauma is a serious clinical problem. Among them, massive hemorrhage is the main cause of disability and death. Globally, 40% of deaths due to injury are caused by massive hemorrhage or its complications. Death caused by bleeding is mostly early death, and more than 60% of deaths occur within 3 hours after injury. Therefore, how to effectively control the early hemostasis of the wounded is particularly important in emergency situations. However, few wound dressings in clinical practice can simultaneously have good hemostatic and wound healing properties. Therefore, it is urgent to develop wound dressings with excellent hemostatic properties and the ability to promote healing. SUMMARY

[0003] An object of the present application is to provide a hydrogel with good hemostatic and wound healing properties in order to solve the above technical problems.

[0004] Another object of the present application is to provide a preparation method of the hydrogel.

[0005] Still another object of the present application is to provide an application of the hydrogel.

[0006] In order to achieve the above objects, the present application provides a rapid hemostatic hydrogel, which comprises microgels and polylysine, the mass ratio of the microgels to the polylysine being 1:2 to 2:1, and the microgels comprising oxidized methyl methacrylic hyaluronic acid and aqueous polyurethane.

[0007] Preferably, the concentration of the oxidized methyl methacrylic hyaluronic acid in the microgels is 4.8%, and the content of the aqueous polyurethane is 4%. That is, 48 milligrams of oxidized methyl methacrylic hyaluronic acid and 0.4 milliliters of aqueous polyurethane are contained in each milliliter of the microgels.

[0008] Preferably, the oxidation degree of the oxidized methyl methacrylic hyaluronic acid is 25%-50%.

[0009] Preferably, the solid content of the aqueous polyurethane is 10-20%.

[0010] Preferably, the molecular weight of the hyaluronic acid in the rapid hemostatic hydrogel is 150,000 to 200,000.

[0011] On the other hand, the present invention also provides a method for preparing the aforementioned fast-acting hemostatic hydrogel, the method comprising the following steps:

[0012] 1) Oxymethyl methacrylate hyaluronic acid and waterborne polyurethane are cross-linked by ultraviolet light to form microgels;

[0013] 2) The microgel is reacted with polylysine in a Schiff base reaction to obtain the fast-acting hemostatic hydrogel.

[0014] Preferably, in step 1), the oxidized methacrylic acid hyaluronic acid is prepared by the following steps: reacting hyaluronic acid with methacrylic anhydride to methylate it, thereby obtaining methacrylic acid hyaluronic acid, and further oxidizing it to oxidized methacrylic acid hyaluronic acid.

[0015] Preferably, in step 1), the specific steps of crosslinking by ultraviolet light are as follows: add waterborne polyurethane and pure water to oxymethacrylic acid hyaluronic acid, stir to dissolve it, add photoinitiator and mix well, then place the mixture at -20°C for 6 to 24 hours, and then take out the frozen mixture and irradiate it with ultraviolet light for 1 to 4 hours to crosslink and form microgels.

[0016] Preferably, in step 1), the waterborne polyurethane is prepared by the following steps: polyethylene glycol 2000 and polycaprolactone 2000 are mixed, vacuum dehydrated, reacted at 110°C for 2 hours, and then cooled to 50°C; isophorone diisocyanate is added and stirred, then dibutyltin dilaurate is added and stirred, the temperature is raised to 75°C, and the reaction is carried out for 2.5 hours; 2,2-bis(hydroxymethyl)propionic acid is added, and the reaction is continued for 1.5 hours; the temperature is lowered to 50°C, 2-hydroxyethyl methacrylate and triethylamine are added, and the reaction is continued for 21 hours; the reaction product is then dropped into pure water to obtain the waterborne polyurethane.

[0017] Preferably, in step 2), the microgel and polylysine are ground together, then a buffer solution is added, stirred evenly, and allowed to stand to form a gel.

[0018] More preferably, the buffer solution is PBS with a pH of 7.4 and a volume of 1 to 2 mL. The grinding time is preferably 10 to 20 minutes, and the stirring time is preferably 1 minute.

[0019] On the other hand, the present invention also provides the use of the aforementioned fast-acting hemostatic hydrogel for hemostasis, particularly for hemostasis of visceral bleeding in animals.

[0020] On the other hand, the present invention also provides the use of the fast-acting hemostatic hydrogel in the preparation of hemostatic products.

[0021] This invention first prepares a waterborne polyurethane (PU) with excellent mechanical properties. Then, through covalent cross-linking of PU with oxidized hyaluronic acid (OMAHA), which provides cell adhesion and growth, and the addition of natural antibacterial polymer polylysine (PL), a novel comprehensive hemostatic hydrogel (OHAMA-PU-PL) with porous structure, combining viscosity, strength, and rapid hemostatic properties is generated. This hydrogel facilitates rapid hemostasis for various wounds. In an acute bleeding model, its hemostasis time for the liver is only 37 seconds, and for the abdominal aorta, it can be controlled within 2 minutes, with a burst pressure reaching 194.52 mmHg. The hydrogel of this invention exhibits excellent hemostatic properties, and its preparation method is simple, requiring no additional solvents or special equipment to complete the reaction. This provides a new approach for the rapid production of natural polymer hydrogels and successfully solves the problem of hemostasis in arterial and visceral bleeding. Attached Figure Description

[0022] Figure 1 Infrared images of OHAMA, PU, ​​and OHAMA-PU-PL, SEM images of the microgel powder of Example 1, and the hemostatic hydrogel of Example 20 are shown.

[0023] Figure 2 The water absorption rate of the hydrogel at different time points is shown.

[0024] Figure 3 The viscosity of the hydrogel is shown in the frequency range of 0.1 ~ 10 Hz.

[0025] Figure 4 The rheological properties of the hydrogels with shear stress range of 0 to 100% are shown.

[0026] Figure 5 Photographs are shown of the hydrogel of Example 20 after being stretched, twisted, and bent on pigskin.

[0027] Figure 6 The adhesion strength on pigskin is shown.

[0028] Figure 7 The burst pressure is shown.

[0029] Figure 8 The results show the BCI index, clotting time, hemostasis status, blood loss, and hemostasis time at different time points in the mouse liver hemostasis experiment for the blank group, gauze group, and hydrogel group.

[0030] Figure 9 The hemostasis test results of hemostatic gauze and hydrogel at different times in the rat abdominal aortic injury model and the bleeding volume and hemostasis time in the liver bleeding model, as well as the SEM characterization of whole blood after interaction with hydrogel (white arrows indicate red blood cells in blood clots).

[0031] Figure 10 The cytotoxicity experiment results are shown. (A) Cell activity statistics after different samples were treated with CCK8; (B) live and dead staining images after different samples were co-cultured with 3T3 cells; (C) hemolysis rate after different samples were co-cultured with blood cells; (D) hemolysis situation after different samples were co-cultured with blood cells. DETAILED DESCRIPTION

[0032] In order to facilitate the understanding of the present application, the present application will be described more fully below in connection with specific embodiments. The present application can be embodied in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided so that this disclosure will be thorough and complete, and fully convey the scope of the application to those skilled in the art.

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used in the description of the application herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The use of the terms "and / or" includes a combination of one or more of the associated listed items.

[0034] Example 1: Preparation of microgels

[0035] A microgel was prepared according to the following steps:

[0036] 1. Preparation of oxidized hyaluronic acid methacrylic acid (OHAMA)

[0037] (1) 1.0 g of hyaluronic acid (HA) (molecular weight can be 150,000 to 200,000, and the hyaluronic acid with a molecular weight of 150,000 was used in this embodiment) was weighed and added to 100 mL of purified water. It was completely dissolved and defoamed by magnetic stirring for 2 hours to obtain a hyaluronic acid solution with a mass concentration of 1%.

[0038] (2) 10 mL (1% of the volume of the hyaluronic acid solution) of methacrylic anhydride (MAA) was added, and then the pH was adjusted to 8 with 10 M NaOH, and the reaction was carried out for 24 hours.

[0039] (3) The mixed solution after reaction was poured into 300 mL (3 times the volume of the hyaluronic acid solution) of ice ethanol, and a precipitate appeared. The precipitate was redissolved and dialyzed in a dialysis bag (Da=3500) with 100 mL of purified water for 3 days, and then freeze-dried to obtain hyaluronic acid methacrylic acid (HAMA).

[0040] (4) Take 1.0 g of HAMA, add 100 mL of pure water, and stir magnetically until it is completely dissolved. Then add 0.5 g of sodium periodate (NaIO4) and continue stirring for 4 hours. Then add 2 mL of ethylene glycol to terminate the reaction, and dialyze for 3 days using a dialysis bag (Da=3500). Freeze-dry to obtain oxidized hyaluronic acid methyl methacrylate (OHAMA) with an oxidation degree of 50% (the oxidation degree can be 25% to 50%, and the amount of sodium periodate added can be adjusted according to the desired oxidation degree). Store at -20°C after drying.

[0041] 2. Preparation of aqueous polyurethane (PU)

[0042] (1) Take 4 mM of polyethylene glycol 2000 (PEG 2000) and 4 mM of polycaprolactone 2000 (PCL 2000) in a three-necked flask, vacuum dehydrate, and react at 110°C for 2 hours, then cool to 50°C.

[0043] (2) Add 19.2 mM of isophorone diisocyanate (IPDI) and stir for 20 min. Add 20 microliters of dibutyltin dilaurate (DBTDL) and stir for 20 min. Then raise the temperature to 75°C and react for 2.5 hours. Add 6 mM of chain extender 2,2-bis(hydroxymethyl)propionic acid (DMPA) and continue to react for 1.5 hours.

[0044] (3) After the temperature drops to 50°C, add 12 mM of 2-hydroxyethyl methacrylate (HEMA) and 3 mM of triethylamine, and continue to react for 21 hours. Then drop the reaction product into 100 mL of pure water (1000 rpm / min, arm stirrer stirring for 1 hour) to obtain aqueous polyurethane (PU). The solid content of the aqueous polyurethane suitable for the present application can be 10% to 20%, preferably 20%, which can be adjusted by changing the amount of pure water added (100 mL to 200 mL).

[0045] 3. Preparation of microgel (OHAMA / PU)

[0046] Add 2 mL of aqueous polyurethane (solid content 20%) and 3 mL of pure water to 240 mg of OHAMA, and stir with a stirring rod until it is dissolved. Add 100 μL of 1% (mass concentration) I2959 (photoinitiator 2959, CAS No. 106797-53-9) and mix well. Place the mixed sample in a freezer at -20°C for 12 hours. Then take out the frozen sample and irradiate it under a UV lamp for 1 hour to crosslink and obtain a microgel. Grind and continue to freeze for 12 hours.

[0047] Example 2

[0048] The present example provides a microgel, the preparation method of which is only different from that of Example 1 in that the ratio of PU and purified water is changed in step "3, preparation of microgel (OHAMA / PU)", which is replaced by adding 1 mL of PU and 4 mL of purified water.

[0049] Example 3

[0050] The present example provides a microgel, the preparation method of which is only different from that of Example 1 in that the ratio of PU and purified water is changed in step "3, preparation of microgel (OHAMA / PU)", which is replaced by adding 3 mL of PU and 2 mL of purified water.

[0051] Example 4

[0052] The present example provides a microgel, the preparation method of which is only different from that of Example 1 in that the ratio of PU and purified water is changed in step "3, preparation of microgel (OHAMA / PU)", which is replaced by adding 4 mL of PU and 1 mL of purified water.

[0053] Example 5

[0054] The present example provides a microgel, the preparation method of which is only different from that of Example 1 in that the mass of OHAMA is changed to 200 mg in step "3, preparation of microgel (OHAMA / PU)".

[0055] Example 6

[0056] The present example provides a microgel, the preparation method of which is only different from that of Example 1 in that the mass of OHAMA is changed to 300 mg in step "3, preparation of microgel (OHAMA / PU)".

[0057] Example 7

[0058] The present example provides a microgel, the preparation method of which is only different from that of Example 1 in that the freezing time of the mixed sample before UV irradiation is changed to 6 hours in step "3, preparation of microgel (OHAMA / PU)".

[0059] Example 8

[0060] The present example provides a microgel, the preparation method of which is only different from that of Example 1 in that the freezing time of the mixed sample before UV irradiation is changed to 18 hours in step "3, preparation of microgel (OHAMA / PU)".

[0061] Example 9

[0062] This example provides a microgel, the only difference between the preparation method of the microgel and Example 1 is that the sample mixing time before UV irradiation is changed to 24 hours in step "3, Preparation of microgel (OHAMA / PU)".

[0063] Example 10

[0064] This example provides a microgel, the only difference between the preparation method of the microgel and Example 1 is that the UV irradiation time is 30 min in step "3, Preparation of microgel (OHAMA / PU)".

[0065] Example 11

[0066] This example provides a microgel, the only difference between the preparation method of the microgel and Example 1 is that the UV irradiation time is 2 hours in step "3, Preparation of microgel (OHAMA / PU)".

[0067] Example 12

[0068] This example provides a microgel, the only difference between the preparation method of the microgel and Example 1 is that the UV irradiation time is 3 hours in step "3, Preparation of microgel (OHAMA / PU)".

[0069] Example 13

[0070] This example provides a microgel, the only difference between the preparation method of the microgel and Example 1 is that the UV irradiation time is 4 hours in step "3, Preparation of microgel (OHAMA / PU)".

[0071] Example 14

[0072] This example provides a rapid-acting hemostatic hydrogel, the preparation method of the rapid-acting hemostatic hydrogel is as follows:

[0073] Take 100 mg of the microgel of Example 1 and 150 mg of polylysine powder, add to a mortar, grind for 10 min, then add 1 mL of buffer solution (PBS, pH 7.4), stir for 1 min, and then stand and wait for gelation.

[0074] Example 15

[0075] This example provides a rapid-acting hemostatic hydrogel, the only difference between the preparation method of the rapid-acting hemostatic hydrogel and Example 14 is that the amount of polylysine powder is 200 mg.

[0076] Example 16

[0077] This embodiment provides a quick-acting hemostatic hydrogel, the preparation method of which is only different from that of Example 14 in that the amount of polylysine powder is 100 mg, and the amount of buffer solution is 0.5 mL.

[0078] Example 17

[0079] This embodiment provides a quick-acting hemostatic hydrogel, the preparation method of which is only different from that of Example 14 in that the amount of microgel is 200 mg, and the amount of polylysine powder is 100 mg.

[0080] Example 18

[0081] This embodiment provides a quick-acting hemostatic hydrogel, the preparation method of which is only different from that of Example 14 in that the amount of polylysine powder is 100 mg, and the amount of buffer solution is 2 mL.

[0082] Example 19

[0083] This embodiment provides a quick-acting hemostatic hydrogel, the preparation method of which is only different from that of Example 14 in that the amount of polylysine powder is 100 mg, and the grinding time is 20 min.

[0084] Example 20

[0085] This embodiment provides a quick-acting hemostatic hydrogel, the preparation method of which is only different from that of Example 14 in that the amount of polylysine powder is 100 mg.

[0086] In the present application, first, a stable microgel basic framework is obtained by covalent cross-linking, and polylysine is grafted into the hydrogel network by using Schiff base reaction, and the cross-linking strength of the three-dimensional network of the hydrogel is strengthened by using the hydrogen bonds formed between the amino groups and the hydroxyl groups, thereby obtaining an injectable quick-acting hemostatic hydrogel product that can be applied to rapid hemostasis.

[0087] Performance test

[0088] The physical properties and efficacy of the quick-acting hemostatic hydrogels prepared in Examples 14-20 are verified.

[0089] The antibacterial performance and coagulation test of the hydrogel are tested according to GB / B 31402-2015 (Plastic surface antibacterial performance test method) and YY / T 1911-2023 (Medical device coagulation test method), respectively.

[0090] Table 1 shows the comparison of the gelation time of the hydrogels of the examples.

[0091] Table 1: Comparison of the gelation time of the hydrogels of the examples

[0092]

[0093] As can be seen from Table 1, with the change of OHAMA and PU concentration, the gelation of hydrogel will also change, and when the mass ratio of microgel powder and polylysine changes, the gelation of hydrogel will also change. The influencing factors also include light time and solution volume; through comparison and final evaluation, it is confirmed that when the microgel: polylysine = 1:1, the grinding time is 10 minutes, and the solution volume is 1 mL, the gelation is best. Therefore, the subsequent performance research will use the hydrogel in Example 20 for determination.

[0094] Figure 1 The infrared images of OHAMA, PU, OHAMA-PU-PL, and the SEM images of microgel powder and hemostatic hydrogel are shown. As shown in Figure 1 , the chemical structures of OHAMA, PU, and OHAMA-PU-PL are characterized by infrared spectrum. OHAMA has 3350 cm 1 (hydroxyl, O—H stretching vibration); 2891 cm 1 (methyl, C—H stretching vibration), indicating that it has a basic HA skeleton; while 1730 cm 1 (aldehyde carbonyl, C=O bending vibration) indicates that it has aldehyde group after successful oxidation; and 1650 cm 1 (double bond, C=C bending vibration) indicates that methylation is successful, thus indicating that the preparation of OHAMA is successful. PU has 3369 cm 1 and 1530 cm 1 (primary amine, N—H stretching vibration and bending vibration), 1234 cm 1 and 1110 cm 1 has C-O-C characteristic peak, 1724 cm 1 (amide carbonyl, C=O stretching vibration), indicating that the synthesis of polyurethane is successful. For OHAMA-PU-PL, 1550 cm 1 (imine, C=H stretching vibration), which indicates that PL is successfully connected to OHAMA-PU through Schiff base. Figure 1 The SEM images of the microgel powder of Example 1 and the hemostatic hydrogel of Example 20 are also shown.

[0095] The water absorption rate of the freeze-dried hemostatic hydrogel was determined at different time points. Figure 2 The water absorption rate of the hemostatic hydrogel of Example 20 at different time points is shown. As can be seen from Figure 2 , the water absorption rate of the hemostatic hydrogel sample is fast, but the total water capacity is not high, only 4 times of the original mass.

[0096] Figure 3 Viscosity of hemostatic hydrogel in the frequency range of 0.1 ~ 10 Hz is shown. When the storage modulus (G') is greater than the loss modulus (G''), the hydrogel is in a gel state. Figure 4 Rheological properties of hydrogel in the shear stress range of 0 ~ 100% are shown. As shown in Figure 3 and Figure 4 When the hemostatic hydrogel of Example 20 is gelled, G' is always greater than G'' as the angular frequency and shear stress increase, indicating that the hemostatic hydrogel of Example 20 can stably appear in a gel state. It is shown that the hydrogel has good mechanical properties to maintain its convenience and integrity. Adhesion performance is very important for hemostasis, and good adhesion can ensure that the formed gel is firmly adhered to the surface of the bleeding tissue without falling off.

[0097] Adhesion tests were performed on different samples. The hemostatic hydrogel of Example 20 was adhered to pigskin for stretching, twisting and bending, and the adhesion state of the hydrogel was observed and the adhesion strength was measured. As shown in Figure 5 and Figure 6 It can be seen that the hemostatic hydrogel of Example 20 has good self-adaptability and tissue adhesion properties to pigskin, and the adhesion reaches 23.5 kPa.

[0098] As shown in Figure 7 Quantitative burst pressure test results show that the hemostatic hydrogel of Example 20 has a higher burst pressure, and the initial value reaches 194.52 ± 5.1 mmHg.

[0099] BCI index can reflect the coagulation performance in vitro. When the material absorbs more red blood cells, there will be fewer red blood cells broken after adding deionized water. Therefore, the lower the absorbance and BCI index, the better the coagulation effect of the hemostatic material. Figure 8 BCI index, coagulation time and hemostatic situation at different time points in mouse liver hemostatic experiment, blood loss and hemostatic time of blank group, gauze group and hydrogel group of Example 20 are shown. As shown in Figure 8 The BCI index of the rapid hemostatic hydrogel 17.69 ± 0.96 is significantly lower than that of the gauze 57.40 ± 1.05 (P < 0.001), indicating that the hydrogel has good coagulation performance (A). Figure 8

[0100] Subsequently, in vitro whole blood coagulation time experiment was carried out to evaluate the coagulation performance of the material. Obviously, the coagulation time of the hydrogel is shortened by more than 35% compared with the gauze group and the blank group (A). Figure 8 ​, B). The mechanism of coagulation can be preliminarily judged according to the red blood cell adhesion experiment: the rapid hemostatic hydrogel can absorb blood components by using its unique porous structure, dehydrate blood rapidly, focus red blood cells and platelets, and promote the formation of physiological hemostasis, i.e. platelet-fibrin clot, by using the positive charge characteristics of PL, so as to seal and stop bleeding.

[0101] The in vivo hemostatic performance of the material was further evaluated by using a mouse liver bleeding model. The left lobe of the mouse liver was cut open with a scalpel to form a 3 mm long and 2 mm deep wound. The hemostatic material was applied to the wound immediately after 2 seconds, and the hemostatic time and bleeding volume of the mouse liver were recorded. Figure 8 Figure 8 As shown in the figures, the hemostatic time of the hydrogel and the blank group was 40±4 seconds and 123±10 seconds respectively. Figure 8 Figure 8 The bleeding volume of the hydrogel was 26±2 mg, and the bleeding volume of the blank group was 199±7 mg respectively.

[0102] A 2-3 mm rat abdominal aortic incision model was established to further evaluate the hemostatic performance of the hydrogel of Example 20. First, the abdominal aorta was isolated and treated with a 5-gauge needle to create a hole. The control group had continuous blood seepage after adding gauze. The hydrogel of Example 20 showed immediate and effective hemostatic and sealing performance, and the wound site no longer bled after 2 minutes, proving that the material has good hemostatic effect on abdominal aortic injury. Figure 9 Figure 9 In addition, the hydrogel of Example 20 had less bleeding volume than the gauze group in this abdominal aortic incision model. Figure 9 Figure 9 The results of the rat liver hemostatic experiment showed that the hydrogel of Example 20 had better hemostatic effect than the gauze group.

[0103] The cytotoxicity experiment was used to observe the effect of the hemostatic hydrogel of Example 20 on cell growth. Figure 10 The cell activity after different samples were cultured for 24 hours and treated with CCK8 is shown in (A), the images of live and dead staining after different samples were cultured with 3T3 are shown in (B), the images after different samples were cultured with blood cells are shown in (D), and the hemolysis rate is shown in (C). ​​​​

[0104] Assessing the cell viability using the CCK-8 colorimetric method, the cell viability reached approximately 100% at different dilutions of the hydrogel, indicating that the hydrogel exhibited weak cytotoxicity at this concentration. The experimental results suggest that the hydrogel extract of Example 20 showed no significant cytotoxicity at different dilutions. Figure 10 A). Furthermore, in hemolysis experiments, this hydrogel was found to have good blood compatibility (…). Figure 10 (C, D).

Claims

1. A fast-acting hemostatic hydrogel, characterized in that... It includes microgels and polylysine, wherein the mass ratio of microgels to polylysine is 1:1, and the microgels include oxymethacrylic acid hyaluronic acid and waterborne polyurethane. The concentration of oxidized methacrylate hyaluronic acid in the microgel is 48 mg / mL, and the volume content of waterborne polyurethane is 40%. The oxidized methacrylate hyaluronic acid was prepared by the following steps: hyaluronic acid was reacted with methacrylic anhydride to methylate it, and then oxidized to oxidized methacrylic acid hyaluronic acid. The oxidation degree of the oxidized methacrylic acid hyaluronic acid is 25%-50%; The solid content of the waterborne polyurethane is 20%.

2. The fast-acting hemostatic hydrogel according to claim 1, characterized in that, The hyaluronic acid in the fast-acting hemostatic hydrogel has a molecular weight of 150,000 to 200,000.

3. The method for preparing the rapid-acting hemostatic hydrogel according to claim 1 or 2, characterized in that... The method includes the following steps: 1) Oxymethyl methacrylate hyaluronic acid and waterborne polyurethane are cross-linked by ultraviolet light to form microgels; 2) The microgel is reacted with polylysine in a Schiff base reaction to obtain the fast-acting hemostatic hydrogel.

4. The method according to claim 3, characterized in that, In step 1), the specific steps of cross-linking by ultraviolet light are as follows: add waterborne polyurethane and pure water to oxymethacrylic acid hyaluronic acid, stir to dissolve it, add photoinitiator and mix well, then place the mixture at -20°C for 6 to 24 hours, and then take out the frozen mixture and irradiate it with ultraviolet light for 1 to 4 hours to cross-link and form microgels.

5. The method according to claim 3, characterized in that, In step 1), the waterborne polyurethane is prepared by the following steps: polyethylene glycol 2000 and polycaprolactone 2000 are mixed, vacuum dehydrated, and reacted at 110°C for 2 hours, then cooled to 50°C; isophorone diisocyanate is added and stirred, then dibutyltin dilaurate is added and stirred, the temperature is raised to 75°C, and the reaction is carried out for 2.5 hours; 2,2-bis(hydroxymethyl)propionic acid is added, and the reaction is continued for 1.5 hours; the temperature is lowered to 50°C, 2-hydroxyethyl methacrylate and triethylamine are added, and the reaction is continued for 21 hours. The reaction product is then dropped into pure water to obtain the waterborne polyurethane.

6. Use of the fast-acting hemostatic hydrogel according to claim 1 or 2 in the preparation of hemostatic products.

Citation Information

Patent Citations

  • Raw material composition and method for preparing bi-crosslinked fibrin adhesive

    CN115671372A

  • Preparation method of ultrasonic-guided injectable degradable hemostatic hydrogel

    CN119455063A